Valutare la capacità di riassumere. Il Summarizing Test, uno strumento per la scuola primaria - Laura Menichetti (LED Edizioni Universitarie, 2018)
The synthesis of the texts is recognised as one of the main processes that contribute to the Reading Comprehension, however in Italian scientific literature (with reference to the context in which the test is to be applied) there is no widespread evidence of suitable tools to evaluate the achievement and possession of this specific competence, nor to evolve and improve it in children. The Summarizing Test, developed within a program aiming at evaluate the effectiveness of the Reciprocal Teaching at primary school, tries to fill this gap. The test validation, realized with data collected from fourth grades in primary schools geographically distributed throughout the Country, gives a glimpse of a promising tool, that could integrate the other reading comprehension tools already available. This paper describes the results of the item analysis carried out in accordance with the Classical Test Theory, and of the split half to allow the usage of two equivalent versions for the pre-test and post-test in the experimental programs.